Genomic alteration of MTAP/CDKN2A predicts sarcomatoid differentiation and poor prognosis and modulates response to immune checkpoint blockade in renal cell carcinoma - Xu, Wenhao; Anwaier, Aihetaimujiang; Liu, Wangrui; Wei, Gaomeng; Su, Jiaqi; Tian, Xi; Xia, Jing; Qu, Yuanyuan; Zhao, Jianyuan; Zhang, Hailiang; Ye, Dingwei (Frontiers in Immunology, 2022)
Sarcomatoid differentiation is a highly aggressive pathological characteristic of renal cell carcinoma (RCC), and is characterized by susceptibility to progression, and extremely poor prognosis. In this study, we included all genomic alteration events that led to a loss of protein function of MTAP and CDKN2A, and enrolled 5,307 RCC patients with genomic sequencing data from Western and Chinese cohorts. Notably, MTAP/CDKN2AMUT occurred in the Chinese population ~2 times more frequently than in the Western cohort and showed significant co-mutation trends. We found significantly higher proportions of sarcomatoid-positive patients with MTAPMUT or CDKN2AMUT compared with MTAP/CDKN2A wild-type (WT) patients (P<0.001). Of the 574 RCC samples from FUSCC cohort and 3563 RCC samples from 17 independent cohorts, the MTAP/CDKN2AMUT significantly predicted extremely poor outcomes (P<0.0001). the Western cohort suggest a concordant relationship between MTAP/CDKN2AMUT and sarcomatoid differentiation in RCC. Moreover, although MTAP/CDKN2AMUT RCC may be insensitive to targeted therapy, the high degree of tumor heterogeneity, and higher PD-L1 and CXCL13 expression characterizations reflected that MTAP/CDKN2A-deficient features could benefit from immunotherapy for patients with RCC. This study utilized RCC samples from large-scale, global, multi-center sequencing cohorts and first proved that MTAP/CDKN2A-deficient significantly correlates with sarcomatoid differentiation in RCC, and predicts aggressive progression, poor prognosis, and primary resistance to targeted therapy and potential favorable responses to immune checkpoints blockade. Unlike conventional targeted therapies, emerging drugs such as immunotherapies or synthetic lethal PRMT5 inhibitors may become novel therapeutic options for patients with MTAP/CDKN2AMUT RCC.